The overlooked manipulation of nucleolar functions by plant pathogen effectors - Ranty-Roby, Sarah; Pontvianne, Frédéric; Quentin, Michaël; Favery, Bruno (Frontiers in Plant Science, 2024)
Pathogens need to manipulate plant functions to facilitate the invasion of their hosts. They do this by secreting a cocktail of molecules called effectors. Studies of these molecules have mostly focused on the mechanisms underlying their recognition and the subsequent transcriptional reprogramming of cells, particularly in the case of R gene-dependent resistance.However, the roles of these effectors are complex, as they target all cell compartments and their plant targets remain largely uncharacterised. An understanding of the mechanisms involved would be a considerable asset for plant breeding. The nucleolus is the site of many key cellular functions, such as ribosome biogenesis, cellular stress regulation and many other functions that could be targets for pathogenicity. However, little attention has been paid to effectors targeting nucleolar functions. In this review, we aim to fill this gap by providing recent findings on pathogen effectors that target and manipulate nucleolar functions and dynamics to promote infection. In particular, we look at how some effectors hijack ribosome biogenesis, the modulation of transcription or alternative splicing, all key functions occurring at least partially in the nucleolus. By shedding light on the role of the plant nucleolus in pathogen interactions, this review highlights the importance of understanding nucleolar biology in the context of plant immunity and the mechanisms manipulated by plant pathogens.